WORKSHOP DAN PENDAMPINGAN IMPLEMENTASI KURIKULUM MERDEKA BAGI GURU PAUD PENAMBANGAN: WORKSHOP DAN PENDAMPINGAN IMPLEMENTASI KURIKULUM MERDEKA BAGI GURU PAUD PENAMBANGAN - Tirtoni, Feri; Luluk Iffatur Rocmah; Rofiqul Halim (Universitas PGRI Adi Buana Surabaya, 2024)
This community service aims to explore strategies for increasing the role of preschool teachers in implementing the independent curriculum. The method used in community service is the socialization method, through this service through the implementation of activities such as seminars and question and answer sessions. The conclusion of this community service reveals that the role of the teacher is the main driver, the essence of the concept of